IMPLEMENTASI MEDIA PEMBELAJARAN LABORATORIUM VIRTUAL DALAM MENDUKUNG PROGRAM MERDEKA BELAJAR PADA SEKOLAH-SEKOLAH DI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Wa Nirmala; Farida Bahalwan; Sriyati Sampulawa; Siti Darmawati; Asmi Ode; Rizky Fatmalasari L; Kasliyanto Kasliyanto; Abdullah Derlean; Pebrywati Watimury (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Learning from home (BDR) conditions make students more exposed to gadgets. This phenomenon is a challenge for teachers to further upgrade their competence in the use of technology. Today's learning requires teachers to develop and apply technology in conducting learning to motivate students. The solution that can be offered from partner problems is to increase the ability to use technology for teachers in junior and senior high schools in Salahutu District, Central Maluku Regency. One of the technologies that can be used in science learning in junior high and high school is a virtual laboratory. The method of activity is in the form of training and assistance in making a virtual laboratory which includes several stages, namely: the preparation stage, the team coaching stage, the training and mentoring stage, the closing stage. Based on the results of the satisfaction questionnaires that were distributed to participants during the evaluation, it was found that the average participants of the training and mentoring activities were able to operate macromedia flash software and create simple Virtual Laboratory applications so that Partner Schools still expect further activities to design IT-based learning media that innovative and can be used in online and offline learning.